Broken social contract: the domestic roots of US hegemonic decline in the world - Werner, Welf; Lammert, Christian (Hegemonic transition, 2025)
When the US established the liberal world order after 1945, it did so on the basis of successful domestic economic and social policies that provided Americans with unprecedented levels of economic growth and participation, as well as increasing social protection. While enjoying the blessings of a widely-uncontested technological leadership, successful countercyclical policies, and growing opportunities in the economic system, US citizens supported American-led multilateral trade liberalization that exposed US labor markets to the cold winds of international competition. The domestic social and economic premises of this socio-economic contract started to crumble in the 1970s. Long-lasting stagflation and mass unemployment challenged the fiscal basis of the welfare regime. The neoliberal turn of the 1980s led to a demolition of welfare services, while the introduction of supply-side economics refocused government policies away from protecting workers to courting global investors. Through financial account liberalization, the demise of the Bretton Woods system invited yet another dimension of international competition that resulted in a power shift from labor to capital. Finally, in a “flat world,” emerging economies constrained the West’s technological and production leadership. Firstly, this chapter argues that the broken socio-economic contract at home made Americans prone to messages of economic nationalism and a retreat from US liberal hegemony in international trade policies. Secondly, the chapter argues that declining support for US-led multilateral trade policies, which emerged over a period of many decades, did not only start with the Trump presidency in 2017, but was synchronized with the deterioration of domestic socio-economic conditions since the 1970s. Finally, and most importantly, this chapter contends that, while long-term structural changes have seriously challenged the domestic social and economic premises of the social contract in the last 50 years, it was the striking policy failure to address these challenges adequately that sets the US experience apart from other more responsive OECD countries.